Eastern Armenian : For the English-speaking world : A contrastive approach - Sakayan, Dora, 1931-; Yerevan State University (Yerevan : Yerevan State University Press, 2007)
[The present textbook aims at teaching Eastern Armenian, the official language of the Republic of Armenia, to adult beginners. Though the mutual is not written specifically with students of Armenian descent in mind, its importance for theyounger generations of Diaspora Armenians cannot be stressed enough].
Includes bibliographical references amd index
Text in English and Armenian
Keywords: East Armenian dialect -- Grammar; Armenian language, Modern -- East Armenian dialect -- Grammar